Navigating from cellular phenotypic screen to clinical candidate: selective targeting of the NLRP3 inflammasome - Rosalie Matico; Karolien Grauwen; Dhruv Chauhan; Xiaodi Yu; Irini Abdiaj; Suraj Adhikary; Ine Adriaensen; Garcia Molina Aranzazu; Jesus Alcázar; Michela Bassi; Ellen Brisse; Santiago Cañellas; et al. (EMBO Molecular Medicine)
Abstract The NLRP3 inflammasome plays a pivotal role in host defense and drives inflammation against microbial threats, crystals, and danger-associated molecular patterns (DAMPs). Dysregulation of NLRP3 activity is associated with various human diseases, making it an attractive therapeutic target. Patients with NLRP3 mutations suffer from Cryopyrin-Associated Periodic Syndrome (CAPS) emphasizing the clinical significance of modulating NLRP3. In this study, we present the identification of a novel chemical class exhibiting selective and potent inhibition of the NLRP3 inflammasome. Through a comprehensive structure–activity relationship (SAR) campaign, we optimized the lead molecule, compound A, for in vivo applications. Extensive in vitro and in vivo characterization of compound A confirmed the high selectivity and potency positioning compound A as a promising clinical candidate for diseases associated with aberrant NLRP3 activity. This research contributes to the ongoing efforts in developing targeted therapies for conditions involving NLRP3-mediated inflammation, opening avenues for further preclinical and clinical investigations.